(untitled) (Jurnal Manajemen dan Ekonomi (JME), 2026)
This study examines the strengthening of village entrepreneurship based on local potential through the sudang lepet business in Sangsit Village, Buleleng Regency, Bali. Village-based entrepreneurship is considered a strategic approach to enhancing local economic resilience by utilizing natural resources, traditional knowledge, and social capital embedded within rural communities. Sudang lepet, a traditionally processed dried shrimp product, represents a form of household-based micro-enterprise that has been managed across generations and remains closely linked to local cultural values. This research aims to analyze entrepreneurial practices of the sudang lepet business, identify internal and external factors influencing business performance, and formulate strategies for strengthening village entrepreneurship based on local potential.The study employs a descriptive qualitative approach with a case study design. Data were collected through observation, in-depth semi-structured interviews, and documentation involving sudang lepet business actors and community figures. Data analysis was conducted using data reduction, data display, and conclusion drawing. SWOT analysis and the Business Model Canvas were applied to support strategic analysis.The findings indicate that the sudang lepet business possesses strong internal advantages, including locally available raw materials, inherited production knowledge, and strong social capital. However, limitations in product innovation, packaging, production scale, and market access constrain competitiveness. The Business Model Canvas reveals a simple yet stable business structure that requires strengthening in value proposition and distribution channels. This study concludes that strengthening village entrepreneurship should adopt a community-based and participatory policy approach, emphasizing capacity building, product standardization, and market development while preserving local cultural identity.